Home and Homelessness in the Work of Charles Dickens - Šmídová, Karolína (Univerzita Pardubice, 2019)
The main concern of the thesis is to depict the perception of home and the experience of loss, by the child protagonist in the selected novels written by Charles Dickens (Oliver Twist, David Copperfield, Nicholas Nickleby). The theoretical part explains terms such as space, place, topophilia, home or homelessness. The practical part analyzes the selected novels and depicts the perception of the home in the childish point of view, and the experience of loss.
Domov a bezdomovectví v díle Charlese Dickense
Keywords: Dickens, Charles; Oliver Twist; David Copperfield; domov; bezdomovectví; topofílie; místo; prostor; Dickens, Charles; Oliver Twist; David Copperfield; home; homelessness; topophilia; place; space